Increased expression of core-fucosylated glycans in human lung squamous cell carcinoma. Issue 38 (16th July 2019) - Ma, Tianran; Wang, Yan; Jia, Liyuan; Shu, Jian; Yu, Hanjie; Du, Haoqi; Yang, Jiajun; Liang, Yiqian; Chen, Mingwei; Li, Zheng
Abstract : The expression level of fucosylated and core fucosylated N -linked glycans increased in lung squamous cell carcinoma tissues. Abstract : Lung cancer is the most frequent cancer and the leading cause of cancer around the world. As one of the major types of lung cancer, lung squamous cell carcinoma (LUSC) is closely associated with smoking and shows poor sensitivity to therapy and prognosis. Although alteration of glycopatterns are reliable indicators of cancer, little is known about the alterations of protein glycosylation related to LUSC. In this study, we compared the differential expression levels of glycopatterns in seven pairs of LUSC tissues and normal pericarcinomatous tissues (PCTs) using lectin microarrays. Fluorescence-based lectin histochemistry and lectin blotting were utilized to validate and assess the expression and distribution of certain glycans in LUSC tissues and PCTs. And we further analyzed their total N -linked glycans using MALDI-TOF/TOF-MS to provide more information about the aberrant glycopatterns. The results showed that the expression level of the core fucosylation recognized by Pisum sativum agglutinin (PSA) and Lens culinaris agglutinin (LCA) was significantly increased in LUSC tissues compared with PCTs. There were 10 and 15 fucosylated N -linked glycans that were detected in PCTs and LUSC tissues respectively, 10 fucosylated N -glycans were common, while five fucosylated N -glycans were unique to LUSC tissues. And the abundance of the fucosylated N -glycans was increased from 40.9% (PCTs) to 48.3% (LUSC). These finding is helpful to elucidate the molecular mechanisms underlying the lung diseases and develop new treatment strategies.